2022
DOI: 10.1177/2156759x221086742
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors Implementing a Trauma-Informed Approach Through Evidence-Based Practices

Abstract: School counselors are well positioned to support students who have experienced trauma, and the need to do so has increased during the past few years. In this article, we provide school counselors with relevant evidence-based practices that are focused on addressing trauma and supporting students who have experienced a traumatic event(s). We also offer strategies for school counselors to implement a trauma-informed approach to align the delivery of services with multitiered systems of support through advocacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Given the disheartening reality that the preventative efforts of school counselors are frequently overlooked, recent studies have actively advocated the roles of school counselors in various school-based prevention programs that grounded in a data-based MTSS framework (Wachter Morris et al, 2021), bullying (Swank et al, 2019), dropout (Rumsey & Milsom, 2019), trauma-informed practice (Alvarez et al, 2022), and substance use (Foss-Kelly et al, 2021). For example, Wachter Morris et al (2021) discussed the educator-counselor identity and explained how this nondual identity assists school counselors in providing implementing suicide prevention programming.…”
Section: Preventionmentioning
confidence: 99%
“…Given the disheartening reality that the preventative efforts of school counselors are frequently overlooked, recent studies have actively advocated the roles of school counselors in various school-based prevention programs that grounded in a data-based MTSS framework (Wachter Morris et al, 2021), bullying (Swank et al, 2019), dropout (Rumsey & Milsom, 2019), trauma-informed practice (Alvarez et al, 2022), and substance use (Foss-Kelly et al, 2021). For example, Wachter Morris et al (2021) discussed the educator-counselor identity and explained how this nondual identity assists school counselors in providing implementing suicide prevention programming.…”
Section: Preventionmentioning
confidence: 99%
“…Alvarez et al (2022) reviewed evidence-based practices for supporting students experiencing traumatic events and suggested using data to identify students who have experienced trauma and offered ways to collaborate and advocate in a multitiered system of supports (MTSS) model with Tier 1, Tier 2, and Tier 3 interventions. Teachers, school counselors, and mental health professionals can co-teach Tier 1 social/emotional learning (SEL) programs and advocate for conflict resolution and decision-making models based on peaceful approaches (Alvarez et al, 2022). The authors also recommended viewing learning from a “trauma-informed lens” to foster resilience (Alvarez et al, 2022, p. 6).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Teachers, school counselors, and mental health professionals can co-teach Tier 1 social/emotional learning (SEL) programs and advocate for conflict resolution and decision-making models based on peaceful approaches (Alvarez et al, 2022). The authors also recommended viewing learning from a “trauma-informed lens” to foster resilience (Alvarez et al, 2022, p. 6).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…School counselors play a significant role in creating a trauma-sensitive school and identifying and supporting students who have experienced trauma (Alvarez et al, 2022; American School Counselor Association [ASCA], 2022c). The ASCA Ethical Standards (ASCA, 2022b) note that school counselors “actively respond to incidents of bias or hate, demonstrating a commitment to equity and promoting a safe, inclusive school community” (p. 5).…”
Section: Introductionmentioning
confidence: 99%
“…Rumsey and Milsom (2018) asserted that school counselors could implement a trauma-informed approach through systemic interventions, targeted school counseling interventions, and collaborative partnerships to support students’ engagement and high school completion. Alvarez et al (2022) suggested specific strategies for school counselors to implement a trauma-informed approach through advocacy and collaboration within multitiered systems of support (MTSS).…”
Section: Introductionmentioning
confidence: 99%